Creating alpha via FA, TA and NA - Leow, Clarence Kai Siang (Nanyang Technological University, 2023)
Fundamental, technical and news analysis are the commonly used strategies by market analysts to identify alpha stocks in the stock market. In this paper, these three analyses were merged to examine the effectiveness in stock investing. Studies of quantitative and qualitative exploration form the ranking methodology based on fundamental analysis for the stocks in the Telecommunication Services sector. Chart patterns, moving average, relative strength index and volume weightage were introduced to perform technical analysis on the stocks of these companies. Economic, political, and business news were also used to analyze the stock trend information. It was determined that the analytical approach of employing fundamental analysis to look into stock fundamentals and technical and news analysis to look into anomalies in price movement was practical and efficient.